The problem of causality in corporate governance research: The case of governance indexes and firm valuation (2015)
In recent years the problem of the determination of causality has become an increasingly important question in the field of corporate governance. This paper reviews contemporary literature on the topic and finds that the current approach is to attempt to determine causality empirically and that the problem remains unresolved. After explaining the reasons why it is not possible to attempt to determine causality using real world data without falling prey to a logical fallacy, this paper discusses an approach to deal with the problem. In particular, the paper argues that the appropriate approach for the problem is to build theories, with causality featuring as a part of those theories, and then to test those theories both for logical and empirical consistency.